Culturally Responsive Special Education - Gerzel-Short, Lydia; Jerae, Kelly; Hovey, Katrina A.; Hsiao, Yun‐Ju; Wei, Yan (Advances in educational marketing, administration, and leadership book series, 2023)
Keywords: dept.sed

Engaging culturally and linguistically diverse families of children with disabilities - Gerzel-Short, Lydia; Kiru, Elisheba W.; Hsiao, Yun-Ju; Hovey, Katrina A.; Wei, Yan; Miller, Rhonda D. (Intervention in School and Clinic, 2019)
Classrooms are increasingly more diverse, and student success can be enhanced through family engagement, especially for culturally and linguistically diverse (CLD) students with disabilities. Too often teachers are stymied by how to engage CLD families of children with disabilities. Common practices of parent involvement are ineffective and fail to appreciate families as members of the educational team. Family engagement seeks to establish and maintain authentic family-school partnerships based on mutual respect and shared agency for student academic and social success. This column provides specific family engagement strategies that teachers and schools can implement in an effort to provide reciprocal collaboration.
9 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000490317000008, lens.org/119-272-627-527-661 tex.address: [object Object] tex.affiliation: [object Object] tex.author-email: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: cultural and linguistic diversity; dept.rdg; dept.sed; disabilities; diverse families; family engagement; family-school collaboration; multicultural; peer-reviewed

Culturally responsive and high-leverage practices: Facilitating effective instruction for English learners with learning disabilities - Wei, Yan; Hovey, Katrina A.; Gerzel-Short, Lydia; Hsiao, Yun-Ju; Miller, Rhonda D.; Kelly, Jerae H. (TESOL Journal)
Research suggests that English learners (ELs) with learning disabilities (LD) may benefit from culturally responsive evidence-based instructional approaches. ELs with LD often present with learning challenges that influence language acquisition and literacy development. One way to address the distinctive proclivities of these students is to consider the importance of culturally responsive evidence-based instruction that can elevate student understanding and academic achievement. This article explores the integration of two theoretical frameworks: culturally responsive practices and high-leverage practices. It then outlines the importance of teacher introspection as an instructional foundation and identifies several strategies for ELs with LD by centering instruction around linguistic assets and cultural values in combination with effective instructional practices. The article concludes with a call to action for teachers to tailor instruction based on students' cultural and language assets, in combination with effective instructional practices to enhance student learning.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/tesj.697 e697 TJ-2020-0319.R3
Keywords: dept.sed; peer-reviewed

Preparing culturally responsive teachers: a systematic review - Miller, Rhonda D.; Gerzel-Short, Lydia; Kelly, Jerae H.; Uphold, Nicole; Hsiao, Yun-Ju; Hovey, Katrina A.; Wei, Yan (Multicultural Learning and Teaching, 2023)
As the world continues to ponder issues of equity and diversity, U.S. public schools face an expanding demographic divide between teachers and students. While diverse groups of public school students show an increase in population, the teaching workforce in the U.S. remains overwhelmingly White. The purpose of this systematic review is to examine how preservice teachers (PST) are being prepared to be culturally responsive. A total of 26 studies published between 2006 and 2020 were reviewed. The results indicate that PSTs’ learning experiences are varied and tend to be stand-alone approaches focused on changing the attitudes and beliefs of PSTs. Findings also bring to light the vagueness of terminology used in the research to define cultural groups of students, the conspicuous absence of studies related to LGBTQ+ populations, and the lack of study replications. Implications for future research are discussed.
Keywords: culturally responsive; dept.sed; diversity; peer-reviewed; pre-service teacher; teacher education; teacher preparation